Irisin Alleviates Cognitive Impairment by Inhibiting AhR/NF-κB-NLRP3-Mediated Pyroptosis of Hippocampal Neurons in Chronic Kidney Disease - Jialing Zhang; Xingtong Dong; Qi Pang; Aihua Zhang (Mediators of Inflammation)
Conclusions: We first demonstrated that irisin alleviated cognitive impairment by inhibiting AhR/NF-κB-NLRP3-mediated pyroptosis of hippocampal neurons in CKD. Overall, irisin may have the potential to serve as a critical antipyroptotic agent for improving CKD-induced cognitive impairment.